COMPARATIVE STUDY OF ANTIBACTERIAL ACTIVITY OF PEEL EXTRACTS OF CITRUS AURANTIUM L. (BITTER ORANGE) AND CITRUS MEDICA L. (LEMON) AGAINST CLINICAL ISOLATES FROM WOUND INFECTION - TUMANE P.M,; MESHRAM V. G,; WASNIK D. D, (International Journal of Pharma and Bio Sciences, 2014)
The main objective of this study is antibacterial activity of Lemon (Citrus medica L.) and Bitter Orange (Citrus aurantium L.) Peel extract against clinical isolates from wound infection. As microorganism are becoming resistant to present day antibiotics, our study focuses on antimicrobial activity and future prophylactic potential of the lemon and orange peels. The antibacterial activity of Peel extract of Citrus medica L. and Citrus aurantium L. were evaluated on bacterial strains like E. coli, Ps. aeruginosa, Kl. pneumoniae, Pr. vulgaris, Serratia marcescens , Propionibacterium acne, Enterococcus spp., Streptococcus spp., S. aureus and S. epidermidis. All bacteria were isolated from wound infected patients and were multiple drug resistant to many antibiotics. Antibacterial activity of five different solvent extracts (Methanol, acetone, ethanol, petroleum ether and n-Hexane) were prepared by using Soxhlet extractor. In-vitro antibacterial activity was performed by agar well diffusion method. Citrus medica peel extracts showed a very good antimicrobial activity when compared to Citrus aurantium. Both plants peel extract showed considerable antibacterial activity against all tested bacteria. The peel extract of Citrus aurantium and Citrus medica can be considered to be as equally potent as the antibiotics used now-a-days